2010
DOI: 10.1007/s10994-010-5211-x
|View full text |Cite
|
Sign up to set email alerts
|

Statistical relational learning of trust

Abstract: The learning of trust and distrust is a crucial aspect of social interaction among autonomous, mentally-opaque agents. In this work, we address the learning of trust based on past observations and context information. We argue that from the truster's point of view trust is best expressed as one of several relations that exist between the agent to be trusted (trustee) and the state of the environment. Besides attributes expressing trustworthiness, additional relations might describe commitments made by the trus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Like the PeerTrust [Xiong and Liu 2004] and RATEWeb [Malik and Bouguettaya 2009] trust evaluation models, ReputationPro adopts a heuristic-based technique to aggregate and average trust ratings as the trustworthiness or reputation values of a seller. Compared to the IHRTM model [Rettinger et al 2011], which is the only multicontext model reported in the literature and adopts statistical and machine learning-based techniques, ReputationPro is much more efficient and thus more suitable to be applied to the dynamic environments of e-commerce applications with millions of users and transactions that are updated every day.…”
Section: Our Approaches and Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Like the PeerTrust [Xiong and Liu 2004] and RATEWeb [Malik and Bouguettaya 2009] trust evaluation models, ReputationPro adopts a heuristic-based technique to aggregate and average trust ratings as the trustworthiness or reputation values of a seller. Compared to the IHRTM model [Rettinger et al 2011], which is the only multicontext model reported in the literature and adopts statistical and machine learning-based techniques, ReputationPro is much more efficient and thus more suitable to be applied to the dynamic environments of e-commerce applications with millions of users and transactions that are updated every day.…”
Section: Our Approaches and Contributionsmentioning
confidence: 99%
“…-Statistical and machine learning-based context-aware trust evaluation: Rettinger et al [2011] propose IHRTM, a context-sensitive trust evaluation model taking advantage of statistical relational learning. In the IHRTM model, contextual information is discussed in the Seller × Item space.…”
Section: Context-aware Trust Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Rettinger et al propose a context-sensitive trust evaluation model (IHRTM) using statistical relational learning [9]. However, a major disadvantage of IHRTM model is its high computational complexity that makes it difficult to be applied to largescale e-commerce websites.…”
Section: A Trust Evaluationmentioning
confidence: 99%
“…In ecommerce environments, different transactions generally have different natures and contexts; even the same seller needs to be considered differently with regard to the trustworthiness in different forthcoming transactions [9], [15]. In addition, the single value computed by these trust evaluation models is static with regard to any forthcoming transaction of selling different products.…”
Section: Introductionmentioning
confidence: 99%